Memperkuat pilar kedisiplinan: Strategi meningkatkan kedisiplinan siswa di Madrasah Aliyah Negeri 2 Lamongan - gita, anandayu (Maliki Interdisciplinary Journal, 2024)
Madrasas as educational institutions have a big role in instilling discipline in their students. This research is intended to describe strategies for improving student discipline, supporting factors for increasing student discipline, and inhibiting factors for increasing student discipline at MAN 2 Lamongan. This research uses a qualitative approach with descriptive methods. Data generated through observation, documentation studies and literature studies. Based on the research results, it can be concluded that several strategies implemented by MAN 2 Lamongan in improving student discipline are the implementation of the 5s program, welcoming students' arrival, familiarization with recitation of the Qur'an and prayer before learning, congregational midday prayers, alternating midday prayers, female studies, istighosah, as well as the final prayer of learning.